Evaluation of joint flexibility and cardiovascular efficiency in children and adolescents with haemophilia and their healthy peers - Mihalova, Eva (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2007)
BACKGROUND: Problems concerning treatment of patients with haemophilia are long-term and exist even in the present days. Thanks to interdisciplinary complex therapy the results of treatment are constantly better than many years ago. AIM: The goal of this study is to analyse the current state of management of haemophilia and to suggest a comprehensive concept of rational and effective rehabilitation of children with haemophilia. METHOD: In the clinical study, two different measurements were used (goniometry and functional step test) and a special questionnaire. Four different groups of participants were created for the clinical measurements (a set of patients and a control group) and for the questionnaire (a set of patients and a control group). RESULTS: This study concluded that there were no significant differences in the outcomes of the goniometry and the step test, and in the restriction of movement activities between the patients and healthy individuals. CONCLUSIONS: The concept of physiotherapy in patients with coagulopathies in the Czech Republic is comparable with rehabilitation concepts in other European and non-European countries. Current rehabilitation care is of good quality and necessary for effective lifelong therapy of haemophilia, however, it is used insufficiently.
Keywords: Physical Fitness; hemofilie A; Exercise Test; lidé; zátěžový test; mladiství; Adolescent; Hemophilia A; Pulse; pulz; Range of Motion, Articular; dítě; Child; rozsah kloubních pohybů; Humans; tělesná výkonnost